A preparation process and method of chloro(bromo)styrene
By using nitrated sulfonic acid resin as a catalyst and combined with the design of the pipeline reactor, the problems of high temperature and harsh conditions in the dehydration reaction of chlorine (bromide)-formed styrene were solved, and the preparation of chlorine (bromide)-formed styrene was achieved with high efficiency and good selectivity, which was suitable for industrial production.
Patent Information
- Application Number
- CN202211560714.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-12-07
AI Technical Summary
The existing methods and routes for preparing chlorine (bromide) styrene by dehydration of chlorine (bromide) styrene by chlorine (bromide) styrene by high operating temperature, harsh reaction conditions, high equipment requirements and product selectivity needs to be improved.
The nitrated sulfonic acid resin is used as a catalyst to achieve the conversion of chlorine (bromide)-styrene to chlorine (bromide)-styrene through a pipeline reactor. The reaction temperature is controlled at 100-220°C, the reaction pressure is at normal pressure, the catalyst activity is high, and the product selectivity is good.
It achieves efficient dehydration reaction at low temperatures, has high product selectivity, is suitable for industrial applications, and avoids the occurrence of side reactions.
Smart Images

Figure CN115772063B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of heterogeneous catalysis and fine chemical manufacturing, and specifically relates to a preparation process and method of chloro(bromo)styrene. Background Art
[0002] Chlorostyrene (bromostyrene) is a monomer for preparing polychlorostyrene (bromostyrene) materials, which can be used to prepare special plastics and rubbers, such as ion exchange resins, functional polymers, photosensitive polymers, polymer catalysts, etc. Chlorostyrene (bromostyrene) is also a common pharmaceutical intermediate, widely used in medicine, pesticides, chemicals and other fields, and has broad market prospects.
[0003] Chloro (bromo) styrene can be prepared by chloro (bromo) benzaldehyde through ylide reaction (Chemische Berichte, 1990, 123: 1441-1442), but the raw material price is expensive, the waste discharge is large, and the industrial application value is not great. Chloro (bromo) styrene can also be prepared by using chloro (bromo) ethylene oxide (Organic Letters, 2012, 14: 22-25) or chloro (bromo) phenylacetylene (Advanced Synthesis and Catalysis, 2012, 354: 1542-1550) as raw materials, but it also faces the problem of raw materials being difficult to obtain. From the perspective of raw materials and environmental protection, the most inexpensive and environmentally friendly route is to reduce chloro (bromo) phenyl ethyl alcohol to obtain chloro (bromo) styrene through dehydration reaction.
[0004] The literature (Fine and Specialty Chemicals 2013, 21, 37-38) reported the use of KHSO4 as a catalyst, at 275°C KHSO4 melting temperature, to dehydrate 4-bromophenylethanol to prepare 4-bromostyrene, with a 4-bromostyrene yield of 90.0% and a purity of 98.4%. Patent (ZL201310018762.X) reported the use of modified aluminum silicate as a catalyst for dehydration, with a reaction temperature of 280°C, requiring -0.08MPa negative pressure operation, and a product purity of 96%. Patent (ZL202110710271.6) reported the route of preparing halogenated styrene using a supported molecular sieve catalyst at 250-330°C, which requires toluene in the reaction system to maintain a good conversion rate and selectivity.
[0005] The methods and routes for preparing chloro(bromo)styrene by dehydrating chloro(bromo)phenylethanol reported in the literature currently face the problems of high operating temperature, harsh reaction conditions, high equipment requirements, and product selectivity that needs to be further improved. Summary of the invention
[0006] In order to solve the above problems, the object of the present invention is to provide a process and method for preparing chloro(bromo)styrene by dehydrating chloro(bromo)phenylethanol using a pipeline reactor. The process uses nitrated sulfonic acid resin as a catalyst. The catalyst preparation process is to obtain resin beads by polymerizing divinylbenzene, followed by sulfonation treatment, and then introduce nitro groups to further enhance the acidity of the resin catalyst to improve the activity of the catalyst. The process of the present invention uses a pipeline reactor to realize the conversion of chloro(bromo)phenylethanol to chloro(bromo)styrene, the process is simple, the operating conditions are mild (the reaction temperature is 100-220°C, and the reaction pressure is normal pressure), the catalyst activity is high, and the product selectivity is good.
[0007] The technical solution of the present invention is:
[0008] A process and method for preparing chloro(bromo)styrene, characterized in that:
[0009] The nitrated sulfonic acid resin is loaded into a pipeline reactor as a catalyst, and chloro(bromo)phenylethanol is introduced to carry out a dehydration reaction to obtain chloro(bromo)styrene.
[0010] The chloro(bromo)phenylethanol raw material is one or more selected from the following structures.
[0011]
[0012] The dehydration reaction temperature is 100-220°C (preferably 120-190°C), the reaction pressure is normal pressure, and the liquid raw material space velocity is 0.01-10.0h -1 (Preferably 0.1 to 5.0h -1 ).
[0013] The pore volume of the sulfonic acid resin catalyst is 0.1-2.0cm 3 / g, preferably 0.3-1.0cm 3 / g, pore size distribution is 0.1-100.0nm, preferably 0.3-10.0nm, specific surface area is 10-1000m 2 / g, preferably in the range of 100-650m 2 / g.
[0014] The preparation process of the sulfonic acid resin catalyst is to obtain resin beads by polymerizing divinylbenzene, followed by sulfonation treatment, and then introducing nitro groups to further enhance the acidity of the resin catalyst to improve the activity of the catalyst.
[0015] The specific steps for preparing the sulfonic acid resin catalyst are:
[0016] a) adding divinylbenzene (CAS No.: 1321-74-0) to an organic solvent under an inert gas atmosphere at 0-50°C, then adding a suspension emulsifier, stirring evenly to form a uniform oil phase to be polymerized; b) dispersing the above oil phase into an aqueous phase under an inert gas atmosphere at 0-150°C, stirring, then adding a free radical initiator, and polymerizing divinylbenzene into polymer pellets by a free radical polymerization method;
[0017] c) filtering out the solid particles in step b), washing them with a solvent 10-100 times the volume of the solid particles, and then removing the solvent under vacuum at 25-120° C. to obtain resin polymer pellets;
[0018] d) Add the resin polymer beads in step c) to the reactor, add 98% concentrated sulfuric acid at 25°C, and react at 100°C for 24 hours. After the reaction is completed, filter out the resin beads, gradient elute to remove the unreacted acid, and finally wash with deionized water until the effluent is neutral. Then vacuum dry at 100-150°C to obtain sulfonated resin polymer beads;
[0019] e) adding the resin polymer pellets in step d) into the reactor, and adding a mixture of concentrated nitric acid and concentrated sulfuric acid (V ) dropwise at 25°C. NNO3 :V H2SO4 =1:1), react at 80 degrees Celsius for 12 hours after the addition is completed. After the reaction is completed, filter out the resin beads, gradient elute to remove the unreacted acid, then wash with deionized water until the effluent is neutral, and finally vacuum dry at 100-150 degrees Celsius to obtain nitrated sulfonic acid resin polymer beads;
[0020] The organic solvent in step a) is one or more of toluene, benzene, xylene, biphenyl and cyclohexane;
[0021] The solvent used for washing the polymer beads in step c) is one or more of toluene, xylene, methanol, ethanol, dichloromethane, water or tetrahydrofuran;
[0022] The inert gas in steps a), b) and d) is selected from one or more of Ar, He, N2 and CO2.
[0023] In step a), before the organic polymer beads are polymerized, the concentration of divinylbenzene in the solvent is in the range of 0.1-100 g / L, and the molar ratio of divinylbenzene to free radical initiator is 10000:1-10:1;
[0024] The suspended emulsifier described in step b) is selected from one or more of polyvinyl alcohol, polyvinyl pyrrolidone, p-octylphenol polyoxyethylene ether, N-dodecyl dimethylamine, sodium stearate and calcium dodecylbenzene sulfonate; the free radical initiator is one or more of cyclohexanone peroxide, dibenzoyl peroxide, tert-butyl hydroperoxide or azobisisobutyronitrile; the volume ratio of the oil phase to the water phase during free radical polymerization is 1000:1-1:1000.
[0025] Reaction principle of the present invention:
[0026] The resin beads obtained by cross-linking divinylbenzene in the present invention have large specific surface area and developed pore structure, which is conducive to the contact between reactants and active sites. At the same time, the acidity of the surface of the resin beads is enhanced by nitrating the sulfonated sulfonic acid resin beads. The nitrated sulfonic acid resin has strong acidity and high catalytic activity for dehydration of chloro(bromo)phenylethanol. The present invention uses a pipeline reactor, and by controlling the residence time, the reactants are removed from the reaction system in time after the reaction is completed, so that the vinyl functional group is prevented from encountering the acidic site and the side reactions such as polymerization occur, so that the product chloro(bromo)phenylethylene has good selectivity.
[0027] The process of the invention adopts a pipeline reactor to realize the conversion of chloro(bromo)phenylethanol to chloro(bromo)styrene, has a simple process, mild operating conditions (reaction temperature of 100-220°C, reaction pressure of normal pressure), high catalyst activity and good product selectivity.
[0028] The beneficial effects of the present invention are:
[0029] The method and route for preparing chloro(bromo)styrene by dehydrating chloro(bromo)phenylethanol reported in the literature at present face the problems of high operating temperature, harsh reaction conditions, high equipment requirements, and product selectivity to be further improved. The present invention adopts nitrated sulfonic acid resin as catalyst, and the catalyst has strong acidity, so the dehydration reaction activity is high. At the same time, a pipeline reactor is used, and the product is not prone to side reactions, so the product selection is good. At the same time, the resin beads prepared by divinylbenzene have a stable structure and good stability. The process and method are suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the N2 physical adsorption curve of the nitrated sulfonic acid resin beads obtained in Example 1 at liquid nitrogen temperature.
[0031] Figure 2 1 is the pore size distribution curve of the nitrated sulfonic acid resin beads obtained in Example 1.
[0032] Figure 3 This is a real-life photo of the nitrated sulfonic acid resin beads obtained in Example 1.
[0033] Figure 4 The present invention is a flow chart of a device for preparing chloro(bromo)styrene by dehydrating chloro(bromo)phenylethanol. DETAILED DESCRIPTION
[0034] The following examples are provided to better illustrate the present invention, but are not intended to limit the scope of the present invention.
[0035] Example 1
[0036] The method for preparing polymer resin beads is as follows:
[0037] At 20°C and inert gas Ar atmosphere, weigh 10g of divinylbenzene (CAS No.: 1321-74-0) and 1.5g of p-octylphenol polyoxyethylene ether (suspension emulsifier) and dissolve them in 50ml of xylene, stir evenly and set aside. At 10°C, under Ar protection, add the xylene solution containing the phosphine ligand into 15ml of deionized water while stirring (mechanical stirring, stirring speed 80r / min), then add 0.1g of azobisisobutyronitrile (initiator), and then continue to stir (mechanical stirring, stirring speed 80r / min) at 90°C for polymerization for 15 hours.
[0038] After cooling to room temperature, the particles were filtered, washed with 500 mL of deionized water, and then vacuum dried at 85° C. for 5 hours to obtain polymer resin beads.
[0039] The preparation method of nitrated sulfonic acid resin beads is as follows:
[0040] Under the protection of inert gas Ar atmosphere at 25°C, weigh 20g of the above polymer resin beads, add 50mL of 98% concentrated sulfuric acid at 25°C, and heat to 100°C to continue the reaction for 24 hours. After the reaction is completed, filter out the resin beads, use 50mL of sulfuric acid solution with mass concentrations of 90%, 70%, 40%, and 5% for gradient elution, and then wash with deionized water until the effluent is neutral. Finally, vacuum dry at 130°C for 5 hours to obtain sulfonated resin polymer beads.
[0041] Under the protection of inert gas Ar atmosphere at 25°C, weigh 20g of the above sulfonated polymer resin beads, add 50mL of a mixture of concentrated nitric acid and concentrated sulfuric acid (V NNO3 :V H2SO4 =1:1), and the temperature was raised to 80°C and the reaction was continued for 12 hours after the addition was completed. After the reaction was completed, the resin beads were filtered out, and gradient eluted with 50 mL of sulfuric acid solution with mass concentrations of 90%, 70%, 40%, and 5%, respectively, and then washed with deionized water until the effluent was neutral. Finally, vacuum dried at 130°C for 5 hours to obtain nitrated sulfonic acid resin polymer beads.
[0042] Figure 1The N2 physical adsorption curve of the nitrated sulfonic acid resin pellets at liquid nitrogen temperature is shown in Figure 2. The specific surface area of the polymer pellets is calculated to be 630.2 m 2 / g, pore volume is 0.99cm 3 / g. Figure 2 This is the pore size distribution curve of the sulfonic acid resin beads after nitration. It can be seen from the figure that the pores of the polymer beads are mainly distributed between 0.2-3nm. Figure 3 This is a real photo of the sulfonic acid resin beads after nitration.
[0043] Example 2
[0044] In Example 2, the polymer resin beads were prepared in the same manner as in Example 1 except that 120 mL of cyclohexane was used instead of 50 mL of xylene.
[0045] Example 3
[0046] In Example 3, when preparing the polymer resin pellets, the mechanical stirring speed was adjusted to 30 r / min, and the rest of the process was the same as in Example 1.
[0047] Example 4
[0048] In Example 4, when preparing the polymer resin beads, 0.1 g of benzoyl peroxide was used instead of 0.1 g of azobisisobutyronitrile as the initiator, and the rest of the process was the same as in Example 1.
[0049] Example 5
[0050] In Example 5, when preparing the polymer resin beads, the free radical polymerization temperature was adjusted from 90° C. to 70° C., and the rest of the process was the same as in Example 1.
[0051] Example 6
[0052] In Example 6, when preparing the polymer resin beads, the free radical polymerization time was adjusted from 15 hours to 30 hours, and the rest of the process was the same as in Example 1.
[0053] Comparative Example 1
[0054] When preparing the polymer resin beads, 10 g of styrene (CAS No.: 100-42-5) was used instead of divinylbenzene (CAS No.: 1321-74-0) as the polymerization monomer, and the rest of the process was the same as in Example 1.
[0055] Comparative Example 2
[0056] Purchase the commonly used industrial The acidic resin of 15(H) (CAS No.: 9037-24-5) was used as a catalyst without any treatment.
[0057] Example 7
[0058] 10.0 g of the catalyst prepared in Examples 1-6 and Comparative Examples 1-2 was loaded into the middle of a pipe reactor (304L material) with an inner diameter of 1 cm, the reactor temperature was raised to 135° C., the raw material p-chlorophenylethanol (structure F in the claims) was introduced, the reaction pressure was normal pressure, and the raw material p-chlorophenylethanol was subjected to dehydration reaction under the conditions of an air velocity of 1.2 h-1, and all the reaction products were collected in a collection tank. The obtained product was analyzed by HP-7890N gas chromatography equipped with an HP-5 capillary column and an FID detector, and the reaction results are listed in Table 1.
[0059] Table 1. Dehydration performance of p-chlorophenylethanol of catalysts of Examples 1-6 and Comparative Examples
[0060]
[0061]
[0062] As can be seen from Examples 1-6, the conversion rate of p-chlorophenethyl alcohol can reach more than 99% using the nitrated sulfonic acid resin as a catalyst, and the purity of the product p-chlorostyrene is more than 99.5. In contrast, the catalyst prepared by using resin beads prepared by cross-linking styrene, sulfonating and then nitrating, has a conversion rate of p-chlorophenethyl alcohol of 70.4% and a product purity of 94.5% (Comparative Example 1), and the remaining byproducts are mainly dimers of styrene. Commercial The acid resin catalyst of 15 (H) has a low conversion rate of p-chlorophenethyl alcohol (21.4%) and a selectivity of p-chlorostyrene of 97.1% (Comparative Example 2). The resin beads obtained by polymerization of sulfonated divinyl after nitration are very suitable for the reaction of catalyzing the conversion of p-chlorophenethyl alcohol to prepare p-chlorostyrene.
[0063] Example 8
[0064] 10.0 g of the catalyst prepared in Example 1 was loaded into the middle of a pipe reactor (304L material) with an inner diameter of 1 cm. The reactor temperature was raised to 135° C., and the following raw materials (AF) were introduced.
[0065]
[0066] The dehydration reaction was carried out under the reaction conditions of normal pressure and raw material space velocity of 1.2h-1, and all the reaction products were collected in a collection tank. The obtained products were analyzed by HP-7890N gas chromatography equipped with HP-5 capillary column and FID detector, and the reaction results are listed in Table 2.
[0067] Table 2. Dehydration performance of chloro(bromo)phenylethanol of catalyst of Example 1
[0068]
[0069] *The reaction temperature was adjusted to 155°C. **The reaction temperature was adjusted to 145°C.
Claims
1. A method for preparing chloro- or bromo-substituted styrene, characterized in that: The nitrated sulfonic acid resin is loaded into a pipeline reactor as a catalyst, and chlorine and / or bromophenylethanol are introduced to carry out a dehydration reaction to obtain chlorine and / or bromostyrene; The chlorine and / or bromine phenylethanol raw material is one or more selected from the following structures, ; The dehydration reaction temperature is 120-190°C, the reaction pressure is normal pressure, and the space velocity of the liquid raw material chlorine and / or bromophenylethanol is 0.1~5.0h -1 ; The pore volume of the sulfonic acid resin catalyst is 0.3-1.0cm 3 / g, pore size distribution is 0.3-10.0nm, specific surface area is 100-650m 2 / g; The preparation process of the sulfonic acid resin catalyst is to obtain resin beads by polymerizing divinylbenzene, followed by sulfonation treatment, and then introducing nitro groups to further enhance the acidity of the resin catalyst to improve the activity of the catalyst.
2. The preparation method according to claim 1, characterized in that: The specific steps for preparing the sulfonic acid resin catalyst are: a) adding divinylbenzene to an organic solvent under an inert gas atmosphere at 0-50°C, and then adding a suspension emulsifier, stirring evenly to form a uniform oil phase to be polymerized; b) dispersing the oil phase into the water phase under stirring at 0-150° C. in an inert gas atmosphere, adding a free radical initiator, and polymerizing divinylbenzene into polymer beads by free radical polymerization; c) filtering out the solid particles in step b), washing them with a solvent 10-100 times the volume of the solid particles, and then removing the solvent under vacuum at 25-120° C. to obtain resin polymer pellets; d) adding the resin polymer beads in step c) into a reactor, adding 95-100% concentrated sulfuric acid dropwise at 20-45° C. under an inert gas atmosphere, and reacting at 70-95° C. for 12-36 hours; after the reaction is completed, filtering out the resin beads, eluting with a sulfuric acid solution having a mass concentration of 90%-5% in a step gradient manner with 2-6 sulfuric acid solutions of different concentrations decreasing in sequence to remove unreacted acid, and finally washing with deionized water until the effluent is neutral; and then vacuum drying at 100-150° C. to obtain sulfonated resin polymer beads; e) adding the resin polymer pellets prepared in step d) into a reactor, and adding a mixture of concentrated nitric acid and concentrated sulfuric acid dropwise at 20-50°C, V HNO3 :V H2SO4 =0.4:1~2.0:1, after the addition is completed, react at 60-95 degrees Celsius for 10-24 hours; after the reaction is completed, filter out the resin beads, use a sulfuric acid solution with a mass concentration of 90%-5% to gradually reduce the concentration of 2-6 sulfuric acid solutions of different concentrations to step gradient elution to remove the unreacted acid, then wash with deionized water until the effluent is neutral, and finally vacuum dry at 100-150°C to obtain nitrated sulfonic acid resin polymer beads.
3. The preparation method according to claim 2, characterized in that: The organic solvent in step a) is one or more of toluene, benzene, xylene, biphenyl and cyclohexane; The solvent used for washing the polymer beads in step c) is one or more of toluene, xylene, methanol, ethanol, dichloromethane, water or tetrahydrofuran; The inert gas in steps a), b) and d) is selected from one or more of Ar, He, N2 and CO2.
4. The preparation method according to claim 2, characterized in that: In step a), before polymerizing into organic polymer beads, the concentration of divinylbenzene in the solvent is in the range of 0.1-100 g / L, and the molar ratio of divinylbenzene to free radical initiator is 10000:1-10:1; The suspension emulsifier in step a) is selected from one or more of polyvinyl alcohol, polyvinyl pyrrolidone, p-octylphenol polyoxyethylene ether, N-dodecyl dimethylamine, sodium stearate and calcium dodecylbenzene sulfonate; the mass ratio of the suspension emulsifier to divinylbenzene is 0.05-0.3; The free radical initiator in step b) is one or more of cyclohexanone peroxide, dibenzoyl peroxide, tert-butyl hydroperoxide or azobisisobutyronitrile; the volume ratio of the oil phase to the water phase during free radical polymerization is 1000:1-1:1000; and the polymerization time is 2-100 hours.
5. The preparation method according to claim 4, characterized in that: The polymerization time is 10-30 hours.
6. The preparation method according to claim 2, characterized in that: Step d) 20 g of resin polymer beads and 20-100 mL of concentrated sulfuric acid; In step e), the mixed solution of 20 g of the resin polymer beads and concentrated nitric acid and concentrated sulfuric acid is 50-200 mL.
Citation Information
Patent Citations
Process for synthesizing chlorostyrene by chlorophenethyl alcohol
CN103936553A
Preparation method and application of supported catalyst for preparing halogenated styrene
CN113333018A